THE OTAGO EXERCISE PROGRAM AND ELDERLY GYMNASTICS ON FALL RISKS YCHOSOCIAL PROBLEMS IN THE ELDERLY - Suwignjo, Aditya Hans; Sari, Deasy Virka (STIKES Telogorejo Semarang, 2024)
Background: Life expectancy is statistical data that describes the average length of time a person lives ina population. The higher the hope rate for a region or country, the better the health and welfare of its people.Objective: To determine the effectiveness of the OTAGO Exercise Program and Elderly Gymnastics on the risk of fallsand psychosocial problems in the elderly.Method: The type of research used is quasi-experimental with a pretest and posttest approach with a control group.Results: Based on the analysis and statistical tests in this study, it can be concluded that the OTAGO Exercise Programand Elderly Gymnastics reduce the risk of falls and psychosocial problems in the elderly.Conclusion: By directing respondents to reduce factors that could worsen the condition, subjects can be taken basedon various criteria, not just the elderly, and the number of research respondents can be increased so that there aremore